Internship Orientation: An Essential Facilitatory Bridging Step for Medical Students - Rajesh Kathrotia (Thieme Medical and Scientific Publishers Pvt. Ltd., 2021)
Background: Internship is a facilitatory period that hones skills and helps in the evolution of a qualified medical student to a competent doctor. The feeling of a final year student joining as a fresh intern after successfully completing the final professional examination will be directionless without a bridging initiative through a buffer program. Fresh interns need to be oriented to the fundamentals of working effectively with a patient as a whole and not as a separate discipline. This study was done to evaluate the effectiveness of the internship orientation program and to assess the feedback of participants about this program. Methodology: This was a study conducted on 235 freshly joined medical interns. The process included evaluation of a well-structured seven-day orientation program by prevalidated structured Multiple Choice Questions (MCQs) and feedback. Results: All interns performed satisfactorily in the post-test with a mean score of 74.13 ± 7.18. Post-test scores were highest for procedure skills and communication skills, including medical ethics. Overall, 232 (99%) of interns responded that the program was useful and it successfully enhanced their clinical skills; 221 (94%) of interns expressed that the content of the program was excellent to good; and 228 (97%) of interns felt that the method used for training was appropriate. Interns also documented that there were a few new skills that were acquired by attending this program. Conclusion: There is an unmet need for an internship orientation program across all medical colleges to lay a strong foundation for naive interns. Based on the results, we recommend an internship orientation program for a smooth and swift transition from that of a medical student to professional life. It will orient the interns and lay the foundation for the next level of assignment in building their professional career. Key Messages: Internship orientation programs are recommended for a smooth and swift transition from that of a medical student to professional life.